Lived experiences of children and adolescents with obsessive–compulsive disorder: interpretative phenomenological analysis - Sravanti, Lakshmi; Kommu, John Vijay Sagar; Girimaji, Satish Chandra; Seshadri, Shekhar (Child and adolescent psychiatry and mental health, 2022)
Background Childhood obsessive–compulsive disorder (OCD) is distinct from OCD in adults. It can be severely disabling and there is little qualitative research on OCD in children. The present study aims to explore the subjective experiences of diagnosis, treatment processes and meaning of recovery in children and adolescents suffering from OCD and provide a conceptual model of the illness. Methods It is a qualitative study of ten children and adolescents selected by purposive sampling. MINI KID 6.0, Children’s Yale-Brown Obsessive–Compulsive Scale and Clinical Global Impression-Severity Scale were administered at the time of recruitment of subjects into the study. Interviews were conducted using an in-depth semi-structured interview guide and audio-recorded. The transcribed interviews were analyzed using Interpretative Phenomenological Analysis (IPA). The study sought to explore participants’ sense-making of their world, their thoughts, feelings and perceptions through interpretative enquiry. The findings were confirmed by a process called investigator triangulation, member check and peer validation. Results IPA yielded five major themes—‘illness perception changes over time’, ‘disclosure on a spectrum’, ‘cascading effects of OCD’, ‘treatment infuses hope and helps’, and ‘navigating through OCD’. A summary of these themes and their subthemes is presented as a conceptual model. The essence of this model is to show the inter-relationship between themes and provide a comprehensive understanding of the phenomenon of OCD. Conclusions To the best of our knowledge, this is the first study to explore lived experiences of children and adolescents with OCD using interpretative phenomenological analysis (IPA). It was noted that perception of illness and treatment processes evolves over time, and recovery is viewed as a process. Future qualitative research can be carried out with a focus on ‘therapist-related barriers’ or ‘student–teacher dyads’ that can inform clinical practice and school policies respectively. Trial registration NIMH/DO/IEC (BEH. Sc. DIV)/2018, l1 April 2018. Key message Delay in recognition of symptoms contributes to significant distress to the individual and family in cases where help is sought. There is a need to improve awareness so as to identify the problems early. This will improve help-seeking behaviour and aid in reducing peer victimization. Therapist-related barriers contribute to delays in making a diagnosis. Treatment is likely to positively impact other spheres of the child’s life such as academics and interpersonal relationships and result in more long-term benefits. Bullying in school-context is a common occurrence.